PENGARUH RETURN ON EQUITY DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Maulida, Nadila; Nurfadillah, Mursidah; Fauziah, Fenty (Jurnal Akuntansi dan Pajak, 2024)
This study aims to determine the effect of ROE (Return on Equity) and CSR (Corporate Social Responsibility) on Stock Prices in mining companies listed on the Bursa Efek Indonesia. The dependent variable used is stock prices. This study also used ROE (return on equity), and CSR (corporate social responsibility) as independent variables. The population in this study is mining companies listed on the Indonesia Stock Exchange in 2019-2022. According to data on www.idx.co.id and based on criteria, there are 27 companies that meet the research requirements. This study was conducted using secondary data from the company for 4 years so that the number of observations was 108 samples